An intellectual history of political corruption - Buchan, Bruce (Political corruption and governance, 2014)
Machine generated contents note: -- Introduction -- 1. Conceptions of Political Corruption in Antiquity -- 2. Patronage, Politics and Perishability in Early Medieval Political Thought -- 3. From Baratteria to Broglio: The Perils of Public Office in Medieval and Renaissance Political Thought -- 4. Affection, Interest and Office in Early Modernity -- 5. Ideological Change in Eighteenth Century Britain -- 6. The Historical Vicissitudes of Corruption -- Conclusion